Reliability of Google Trends: Analysis of the Limits and Potential of Web Infoveillance During COVID-19 Pandemic and for Future Research - Rovetta, Alessandro (Frontiers in Research Metrics and Analytics, 2021)
Alongside the COVID-19 pandemic, government authorities around the world have had to face a growing infodemic capable of causing serious damages to public health and economy. In this context, the use of infoveillance tools has become a primary necessity. The aim of this study is to test the reliability of Google Trends. The paper focuses on the analysis of relative search volumes (RSVs) quantifying their dependence on the day they are collected. RSVs of the query "coronavirus + covid" during February 1 - December 4, 2020 (period 1), and February 20 - May 18, 2020 (period 2), were collected daily by Google Trends from December 8 to 27, 2020. The survey covered Italian regions and cities, and countries and cities worldwide. The search category was set to all categories. Pearson and Spearman correlations between RSVs and the number of COVID-19 cases were calculated day by day thus to highlight any variations related to the day RSVs were collected. Student t-test was used to assess the statistical significance of the differences between the average RSVs of the various countries, regions, or cities of a given dataset. The percentage increase Δ was used to quantify the difference between two values. Google Trends has been subject to an acceptable quantity of anomalies only as regards the RSVs of Italian regions and countries worldwide. However, the correlations between RSVs and COVID-19 cases underwent significant variations even in these two datasets. Furthermore, only RSVs of countries worldwide did not exceed confidence threshold. Finally, the large amount of anomalies registered in Italian and international cities’ RSVs made these datasets unusable for any kind of statistical inference. In the considered timespans, Google Trends has proved to be reliable only for surveys concerning RSVs of countries worldwide. Since RSVs values showed a high dependence on the day they were gathered, it is essential for future research that the authors collect queries’ data for several consecutive days and work with their RSVs averages instead of daily RSVs, trying to minimize the standard errors until an established confidence threshold is respected. Further research is needed to evaluate this method.